Evaluation of Musculoskeletal and Pulmonary Bacterial Infections With [I]FIAU PET/CT - Steve Y. Cho MD; Steven P. Rowe MD, PhD; Sanjay K. Jain MD; Lew C. Schon MD; Rex C. Yung MD; Tariq A. Nayfeh MD, PhD; Clifton O. Bingham MD; Catherine A. Foss PhD; Sridhar Nimmagadda PhD; Martin G. Pomper MD, PhD (Molecular Imaging)
Purpose: Imaging is limited in the evaluation of bacterial infection. Direct imaging of in situ bacteria holds promise for noninvasive diagnosis. We investigated the ability of a bacterial thymidine kinase inhibitor ([ 124 I]FIAU) to image pulmonary and musculoskeletal infections. Methods: Thirty-three patients were prospectively accrued: 16 with suspected musculoskeletal infection, 14 with suspected pulmonary infection, and 3 with known rheumatoid arthritis without infection. Thirty-one patients were imaged with [ 124 I]FIAU PET/CT and 28 with [ 18 F]FDG PET/CT. Patient histories were reviewed by an experienced clinician with subspecialty training in infectious diseases and were determined to be positive, equivocal, or negative for infection. Results: Sensitivity, specificity, positive-predictive value, negative-predictive value, and accuracy of [ 124 I]FIAU PET/CT for diagnosing infection were estimated as 7.7% to 25.0%, 0.0%, 50%, 0.0%, and 20.0% to 71.4% for musculoskeletal infections and incalculable-100.0%, 51.7% to 72.7%, 0.0% to 50.0%, 100.0%, and 57.1% to 78.6% for pulmonary infections, respectively. The parameters for [ 18 F]FDG PET/CT were 75.0% to 92.3%, 0.0%, 23.1% to 92.3%, 0.0%, and 21.4% to 85.7%, respectively, for musculoskeletal infections and incalculable to 100.0%, 0.0%, 0.0% to 18.2%, incalculable, and 0.0% to 18.2% for pulmonary infections, respectively. Conclusions: The high number of patients with equivocal clinical findings prevented definitive conclusions from being made regarding the diagnostic efficacy of [ 124 I]FIAU. Future studies using microbiology to rigorously define infection in patients and PET radiotracers optimized for image quality are needed.